Strategi Ekspansi Bisnis Start Up Internasional Berkelanjutan: pengabdian kepada Masyarakat - Muhammad Tohir; Ade Abdullah Suryobuwono; Cecep Pahrudin; Irwan Chairuddin; Sugiyanto Sugiyanto (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2026)
The digital economic transformation has created vast opportunities for startups to expand their business activities beyond domestic markets. However, the process of entering international markets entails various challenges, including cultural and consumer behavior differences, cross-border regulations, resource constraints, competitive dynamics, and demands for responsible and sustainable business practices. This Community Service activity aimed to foster understanding and enhance the readiness of practitioners, academics, business owners, and students in formulating startup internationalization strategies that are adaptable to change and sustainability-oriented. The event was held online via Zoom on August 20, 2026, involving approximately 60 participants from diverse backgrounds. The program featured presentations, discussions, case studies, and Q&A sessions focusing on the opportunities and challenges of cross-border business development. Topics covered included business model readiness, target market mapping, innovation, digital technology utilization, human resource competency strengthening, partnership network building, risk management, and the implementation of sustainability principles. The results indicate that participants gained a better understanding of the importance of evaluating organizational readiness and market conditions before determining expansion goals. Participants also recognized that leveraging digital technology can facilitate market expansion, improve business process efficiency, and help companies gain insights into consumer needs. Furthermore, sustainability was viewed as a strategic element capable of strengthening a company's reputation and long-term competitiveness. Thus, this activity underscores that startup internationalization requires an integrated approach combining innovation, technology, human resources, collaboration, risk management, and sustainability to build a competitive business in the global market.